Community effectiveness of pyriproxyfen as a dengue vector control method: a systematic review - Maoz, Dorit; Runge-Ranzinger, Silvia; Horstick, Olaf (PLoS neglected tropical diseases, 2017)
Author summary: There is evidence that pyriproxyfen may effectively reduce the density of immature mosquito stages when applied to identified breeding sites. Various formulations are commercially available, and easy to use without a health threat to the user. However, questions remain regarding its use as a single agent in a community setting. Considering its mode of action, it would not be the product of choice for use in an acute outbreak setting. However, for a sustainable community approach, especially slow-release pyriproxyfen formulations seem promising, because they are the longest lasting choice. The analysis suggests, that combination with a second vector control chemical, preferably an adulticide tackling different stages of mosquito development, increases the efficacy of pyriproxyfen and prolongs the duration of a single application. This systematic literature review clearly shows that there is a need for further studies, preferably utilising cluster-randomised controlled (cRCT) designs, to investigate the community effectiveness of pyriproxyfen and to link entomological outcomes to human dengue transmission.